A new species of jambú (Acmella, Heliantheae, Asteraceae) from Amazonia, Brazil - Campos, Markus M.; Fernandes, Géssica E.a.; Hall, Climbiê F.; Dos Santos, João U.m. (Phytotaxa, 2019)
While studying the tribe Heliantheae (Asterecaceae) in the Brazilian Legal Amazon, a new species of Acmella was discovered. This and three other species of the genus are popularly known as jambú and used in the local cuisine. This work provides an identification key, a detailed description, comments and an illustration of the new species. Based on what is known, the species is endemic to Pará and, consequently, to the Brazilian Legal Amazon.